Scrutinizing Indonesian pre-service teachers’ technological knowledge in utilizing AI-powered tools - Hastomo, Tommy; Mandasari, Berlinda; Widiati, Utami (Journal of Education and Learning (EduLearn), 2024)
Educators have widely adopted artificial intelligence (AI) as a product of technology to prepare teaching materials and enhance their understanding of technology integration in language teaching. As prospective teachers who may teach digital native students later, pre-service teachers must be more capable and knowledgeable in technologically-based pedagogy, materials, and assessment. This study aimed to explore English as a foreign language (EFL) pre-service teachers’ technological knowledge of utilizing AI-powered tools using the technological pedagogical content knowledge (TPACK) framework and investigate their strategies in the advanced of their technological knowledge. This mixed-method research design employed a five-point Likert scale questionnaire and a semi-structured interview as instruments to collect data. Fifty-five EFL pre-service teachers were purposively selected. Data from the questionnaire were analyzed statistically and descriptively, and data from interviews were analyzed thematically. The first findings of this study comprehensively revealed that EFL pre-service teachers exhibit a moderate level of proficiency in addressing technological knowledge (TK), technological pedagogical knowledge (TPK), technological content knowledge (TCK), and TPACK in utilizing AI-powered tools. Meanwhile, the second finding revealed that the participants employed four key strategies to advance their technological knowledge using AI-powered tools: engaging in TPD programs, collaborating with tech-savvy colleagues, staying informed about AI trends, and experimenting with AI-powered tools.